First Communion Celebrations in Manggarai Flores and The Pastoral Implications on Faith Family Education - Fransiska Widyawati; Yohanes S. Lon (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2025)
The Eucharist, one of the seven sacraments in the Catholic Church, holds a central and pivotal role in Christian life. Through this sacred ritual, Christians find communion with Christ, who is presented in the consecrated bread and wine. The celebration of the Eucharist is fundamental to the spiritual journey of believers. When a child receives their first communion, the church marks this significant milestone with great enthusiasm. Simultaneously, parents also take part in the celebration. This article explores the diverse ways in which Flores parents in East Nusa Tenggara celebrate their child's first communion. This research employed ethnography as the research methodology, with observations and interviews as the tool to collect data. Our findings revealed various ways of celebrating the first communion within the community. Among then, parties were the prevailing mode of celebration. Each celebration carried both positive and negative implications. While parties fostered familial prestige, they could also be wasteful and fail to prioritize child-friendliness. Regrettably, these festivals often lean more toward adult-oriented gatherings rather than child-centered or spiritually enriching events. As the conclusion, the First Communion ceremony among the Flores people transcended their religious practice; it transformed into a joyous occasion that involved the entire family and served as a social gathering. Given the potential drawbacks of excessive partying, the church should implement a pastoral strategy that emphasizes comprehensive family faith education and eucharistic understanding.